Analisis Perilaku Struktur Bangunan Terhadap Beban Gempa Pada Bangunan Soft Second Story Dengan Variasi Ketinggian Kolom - Dian Yuristia; Ririt Aprilin S; R. Eka Murtinugraha (Menara: Jurnal Teknik Sipil, 2018)
The purpose of this research was to analyze soft second story bulding behavior due to the earthquake load by applying column height variation. The building case has a vertical irregularity soft story on the second level so the behavior during the earthquake was analyzed by heighten the columns at the second level of the building. The behavior of building structure results the response such as internal forces in columns and beams, base shear, fundamental period, displacement and story drift. The seismic analysis is using dynamic analysis response spectrum based on SNI 1726:2012 and carried out using software ETABS version 9.7.4. The results of this research indicates that the increase of column height in soft second story building reduces the building stiffness. So it decreases the building forces, extending the fundamental period, decreasing the base shear, increasing the displacement and the story drift. It can be concluded that the soft second story building reduces the building resistance of earthquake load by produces the behavior approaches the collapse.